A Case Study on Outpatient Waiting Time for Treatment with Single Server Queuing Model at Public Eye Hospital in Bangladesh - Haque, Obaidul; Akter, Sharmin; Hossen, Anwar; Rahman, Zillur (American Scientific Research Journal for Engineering, Technology, and Sciences, 2020)
In public hospital outdoor patient services all over the world have become an important component of health care. Queuing is a major challenge for healthcare service particularly in developing countries, queuing theory helps decision making to improve waiting problem is not commonly used by managers in developing countries in contrast to their counterparts in the developed world. In this paper we introduce data analysis of observation to reduce outdoor patients waiting time without cost consideration at public hospital.